Assessing the impact of industrial pollution stress on the physiological defense, proximate composition and morphological traits of riparian vegetation - Anum Sajid; Kafeel Ahmad; Zafar Iqbal Khan; Ahlam Khalofah; Iftikhar Ahmad (BMC Plant Biology)
Abstract The untreated disposal of industrial effluents that contain hazardous toxic metal elements such as cadmium (Cd), chromium (Cr), lead (Pb), nickel (Ni), manganese (Mn) and iron (Fe), causes major threats to the ecosystem. The present study aims to focus on the health of water bodies and riparian vegetation in the Sargodha district. Industrial effluents from sugar mill industries drain the Jhelum River and eventually pose a major threat to the riparian vegetation of the area as it does in other parts of the world. The results suggested the presence of a high level of pollution in drains carrying the industrial effluents and inside the river in the form of increased salinity, metal toxicity, and the acidic and alkaline nature of industrial drainage. Additionally, a few acclimated species such as Eclipta alba, Desmostachya bipinnata, Cynodon dactylon, Paspalum distichum, and Cyperus rotundus were identified and examined for their physiological, proximate, and morpho-anatomical attributes. Most of the species exhibit a high degrees of anatomical modification, such as sclerification and aerenchyma formation which support their survival in such a polluted environment. These plants presented increased production of crude fibers, carbohydrates, and proteins, as well as enhanced photosynthetic pigments, allowing them to cope with stress conditions. This study highlights the need for urgent measures to mitigate the impact of industrial pollution on the environment and ecosystem, and underscores the importance of identifying and conserving plant species that can tolerate and adapt to polluted conditions.